2020
DOI: 10.1111/jne.12823
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic stimulation of kisspeptin neurones within the posterodorsal medial amygdala increases luteinising hormone pulse frequency in female mice

Abstract: Kisspeptin within the arcuate nucleus of the hypothalamus is a critical neuropeptide in the regulation of reproduction. Together with neurokinin B and dynorphin A, arcuate kisspeptin provides the oscillatory activity that drives the pulsatile secretion of gonadotrophin‐releasing hormone (GnRH), and therefore luteinising hormone (LH) pulses, and is considered to be a central component of the GnRH pulse generator. It is well established that the amygdala also exerts an influence over gonadotrophic hormone secret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 42 publications
3
58
0
Order By: Relevance
“…Moreover, stress decreases inhibitory GABAergic control within the amygdala leading to enhanced inhibitory efferent output from the amygdala (42,43). Kisspeptin signalling in the MePD regulates GnRH pulse generator frequency (44) and recently we have shown selective optogenetic stimulation of MePD kiss1 neurons increases LH pulse frequency (19). Direct neural projections, of unknown phenotype, extend from the MePD to kiss1 neurons in the ARC (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, stress decreases inhibitory GABAergic control within the amygdala leading to enhanced inhibitory efferent output from the amygdala (42,43). Kisspeptin signalling in the MePD regulates GnRH pulse generator frequency (44) and recently we have shown selective optogenetic stimulation of MePD kiss1 neurons increases LH pulse frequency (19). Direct neural projections, of unknown phenotype, extend from the MePD to kiss1 neurons in the ARC (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is modulation of the reproductive axis by the MePD may involve a disinhibitory system whereby kiss1 neuron activity in the MePD stimulates inhibitory GABAergic interneurons which in turn inhibit GABAergic efferents from the MePD to the ARC, thus allowing for the observed increase in GnRH pulse generator frequency in response to activation of MePD kiss1 neurons (19). Conversly, reduced kisspeptin signalling in the MePD, as with kisspeptin antagonism, decreases GnRH pulse generator frequency (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Kiss1 ARC neurons are predominantly glutamatergic (9,10) and have the potential to release the fast-acting transmitter glutamate onto (1) neighboring neurons in the ARC to potentially regulate metabolism (discussed in later sections), and (2) Kiss1 AVPV/PeN neurons to regulate fertility (10,11). An additional population of Kiss1 neurons has been recently identified in the posterodorsal part of the medial amygdala (Kiss1 MePD (12)), and a number of chemogenetic (13) and optogenetic (14) studies by our lab and others suggest an important role of Kiss1 MePD signaling in the regulation of the GnRH pulse generator, besides a potential role in driving emotional and sexual behavior, pubertal timing and ovulation -at least in mice (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…This amygdaloid nucleus is also known to project to the KNDy neural population in the ARC ( 17 , 18 ). Extrahypothalamic kiss1 neuronal populations exist in the MePD, and we have recently shown that optogenetic stimulation of these neurons increases LH pulse frequency in mice ( 19 ).…”
mentioning
confidence: 99%